Oribatids from the Carpathian Basin with zoogeographical and taxonomical notes (Acari: Oribatida) - Mahunka, S. (Opuscula Zoologica Instituti Zoosystematici et Oecologici Universitatis Budapestinensis, 2006)
A list of oribatids collected at several sites in the Carpathian Basin includes 32 species. The researches yielded some species new for the area examined and two (Dissorhina longispina and Conchogneta vasiliorum spp. n.) new to science. Some taxonomical notes on rare or little known species (e.g. in family Autognetidae) and notes on zoogeographical distribution of some species are presented. With 20 figures.